2019
DOI: 10.1007/s12035-019-01731-5
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of CNS-Specific PPARGC1A Transcripts Is Regulated by Hypoxia and a Variable GT Repeat Polymorphism

Abstract: PPARGC1A encodes a transcriptional co-activator also termed peroxisome proliferator-activated receptor (PPAR) gamma coactivator 1-alpha (PGC-1α) which orchestrates multiple transcriptional programs. We have recently identified CNS-specific transcripts that are initiated far upstream of the reference gene (RG) promoter. The regulation of these isoforms may be relevant, as experimental and genetic studies implicated the PPARGC1A locus in neurodegenerative diseases. We therefore studied cis-and trans-regulatory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 89 publications
0
19
0
Order By: Relevance
“…PGC-1α expression can also be enhanced in striatal SPNs in response to cocaine exposure, with changes being selective for neurons expressing dopamine receptor Drd1 [ 87 ]. Accumulating evidence also indicates the existence of brain-specific splice variants of PGC-1α [ 88 ] that are responsive to cellular stimuli, such as hypoxia [ 89 ], although the cell-type-specific distribution of these variants has not yet been determined. The cell-type-specific expression patterns of PGC-1α as well as its potential non-mitochondrial roles in neuron function are important to acknowledge when assessing therapeutic overexpression or targeting of PGC-1α for neuroprotection (see below).…”
Section: Identification Of Neuron-enriched Pgc-1α-dependent Transcmentioning
confidence: 99%
“…PGC-1α expression can also be enhanced in striatal SPNs in response to cocaine exposure, with changes being selective for neurons expressing dopamine receptor Drd1 [ 87 ]. Accumulating evidence also indicates the existence of brain-specific splice variants of PGC-1α [ 88 ] that are responsive to cellular stimuli, such as hypoxia [ 89 ], although the cell-type-specific distribution of these variants has not yet been determined. The cell-type-specific expression patterns of PGC-1α as well as its potential non-mitochondrial roles in neuron function are important to acknowledge when assessing therapeutic overexpression or targeting of PGC-1α for neuroprotection (see below).…”
Section: Identification Of Neuron-enriched Pgc-1α-dependent Transcmentioning
confidence: 99%
“…Our understanding of the function of PGC1α in the brain is still emerging. Despite findings describing multiple and uniquely regulated transcriptional PGC1α isoforms in the brain (Soyal et al, 2020;Soyal et al, 2012;Soyal et al, 2019), their function remain largely unknown. Full body and CNS-conditional Pgc1α KO mice were generated over a decade ago and found to have neurological phenotypes, including altered behaviour, but inconsistent data has been reported by different groups (Dougherty et al, 2014;Leone et al, 2005;Lin et al, 2004;Lucas et al, 2012;Lucas et al, 2010;Lucas et al, 2014b;McMeekin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, HIF1α was recently shown to activate transcription from the human B1 promoter, which corresponds to the SSR promoter in the mouse, by selectively interacting with it and not the reference promoter for the gene (Soyal et al, 2020). While the role of HIF1α in the brain has previously been limited to hypoxic insult, a recent study has shown that crucial polarity-controlled events in neuronal determination and cerebellar germinal zone exit -including spindle orientation during neural stem cell division, axon-dendrite specification, or adhesive events that promote synaptogenesis (Singh et al, 2016;Singh and Solecki, 2015;Uzquiano et al, 2018) are also regulated through HIF1α-dependent pathways, and, consequently, are sensitive to O2 tension (Kullmann et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations